The Effects Of Single Loop And Double Loop Learning With Peer Scaffolding In Problem-Based Gaming On Science Process Skills Among Fifth Grade Students - Rahmani, Raheleh (2013)
The purpose of this study is to investigate the mechanisms of engagement in problem-based gaming with scaffolding and their effects on basic and integrated science process skills. Problem-based gaming (PBG) postulates that players engage in single-loop learning (SLL) and double-loop learning (DLL) when they solve problems through the various levels of a game. A quasi-experimental study involving two intact classes was employed with a sample comprising 72 male and female fifth-grade pupils. One class was assigned to play the game individually and the other in pairs, with the pupils choosing their own partners. An evaluation of the students’ achievement in science indicated significant differences between the two classes. Therefore, the students’ science achievement scores were used as a covariate. The independent variable was peer scaffolding, and the dependent variables were the learner’s intensity of reflection, levels of engagement in the game in the form of single-loop learning and double-loop learning, and performance in basic and integrated science process skills. The instruments consisted of the Ohio achievement assessments of science (2007) for grade 5 to evaluate the performance of students in basic and integrated process skills, a game-playing log to record reward points for each level and evaluate the level of engagement during the game, and a reflection questionnaire. Further analysis was conducted to investigate the performance in basic and integrated science process skills by the level of engagement in single-loop learning and double-loop learning.